Acarbose improves health and lifespan in aging HET3 mice. Issue 2 (27th January 2019) - Harrison, David E.; Strong, Randy; Alavez, Silvestre; Astle, Clinton Michael; DiGiovanni, John; Fernandez, Elizabeth; Flurkey, Kevin; Garratt, Michael; Gelfond, Jonathan A. L.; Javors, Martin A.; Levi, Moshe; Lithgow, Gordon J.; et al.
Abstract: To follow‐up on our previous report that acarbose (ACA), a drug that blocks postprandial glucose spikes, increases mouse lifespan, we studied ACA at three doses: 400, 1, 000 (the original dose), and 2, 500 ppm, using genetically heterogeneous mice at three sites. Each dose led to a significant change (by log‐rank test) in both sexes, with larger effects in males, consistent with the original report. There were no significant differences among the three doses. The two higher doses produced 16% or 17% increases in median longevity of males, but only 4% or 5% increases in females. Age at the 90th percentile was increased significantly (8%–11%) in males at each dose, but was significantly increased (3%) in females only at 1, 000 ppm. The sex effect on longevity is not explained simply by weight or fat mass, which were reduced by ACA more in females than in males. ACA at 1, 000 ppm reduced lung tumors in males, diminished liver degeneration in both sexes and glomerulosclerosis in females, reduced blood glucose responses to refeeding in males, and improved rotarod performance in aging females, but not males. Three other interventions were also tested: ursolic acid, 2‐(2‐hydroxyphenyl) benzothiazole (HBX), and INT‐767; none of these affected lifespan at the doses tested. The acarbose results confirm and extend our original report, prompt further attention to the effects of transient periods of high blood glucose on aging and the diseases of aging, including cancer, and should motivate studies of acarbose and other glucose‐control drugs in humans.